A/r/tography as indisciplinary turning. Issue 2 (1st June 2014) - Kalin, Nadine M.
This article considers the disciplinary disturbances of recent turns in contemporary art in relation to processes of a/r/tographical enquiry. Specifically, it looks at the pedagogical and socially engaged turns in art practices that reverberate with the multiple disciplines that can exist within a/r/tography. These sites of disturbance are contrasted with the disciplinary debates that include traditional schools of art and design in order to delve further into notions of knowledge production and reproduction within disciplines yet to come aimed to inspire gatekeepers at universities towards reinvention. Moreover, the potentialities of Derrida's iterability and Rancière's indisciplinary knowledge are described as concepts significant to a rethinking of a/r/tography in ways that demonstrate Rogoff's notions of the repractising and relocalization of disciplines through enquiry. Throughout, this article is structured as a series of interconnected turns that engage a/r/tography theoretically, artistically and disciplinarily in an expansive and speculative manner in order to animate methodological possibilities while stimulating disruptive movement generated within indisciplinary turning.